A comprehensive review of reactive flame-retardant epoxy resin: fundamentals, recent developments, and perspectives - Zhi, Maoyong; Yang, Xiong; Fan, Rong; Yue, Shan; Zheng, Lingling; Liu, Quanyi; He, Yuanhua (Polymer degradation and stability, 2022)
•Fundamentals of reactive flame-retardant epoxy resin are comprehensive illustrated.•The review of research literatures published in recent five years are conducted.•Current status, challenges and future perspectives are analyzed and presented.•Further research focuses on environmentally friendly flame-retardant technology. Epoxy resins are widely used in many fields because of their excellent physical and chemical properties. Unfortunately, epoxy resins are inherently combustible materials and have great fire hazard. Three methods are employed to endow epoxy resins with good flame-retardant properties, and they are intrinsic flame-retardant, additive flame-retardant and reactive flame-retardant. Reactive flame-retardant epoxy resins become a research trend due to their good flame-retardant, thermal stability and mechanical properties. In this review, the combustion process, flame-retardant mechanism and classification of flame-retardant epoxy resins are briefly analyzed. Several important characterization methods of flame-retardant epoxy resins are introduced. Importantly, the latest research progresses of reactive flame-retardant epoxy resins are summarized and discussed, including halogen-, phosphorus-, nitrogen-, silicon-, multi-elements containing, and bio-based flame-retardant epoxy resins. Furthermore, the future perspectives of reactive flame-retardant epoxy resins are put forward. This work may provide some new insights for the design of reactive flame-retardant epoxy resins. [Display omitted]